Detection of Brucellosis in Dairy Cattle in Turen District Malang Regency using Rose Bengal Test (RBT) and Complement Fixation Test (CFT) Methods - Kusumastuti, Imbi; Tyasningsih, Wiwiek; Praja, Ratih Novita; Suwarno, Suwarno; Yunita, Maya Nurwartanti; Yudhana, Aditya (Universitas Airlangga, 2021)
The purpose of this research was to detect Brucellosis in female dairy cattle in Turen District, Malang Regency. A total of 78 samples were used in this research taken from 351 total population of female dairy cattle that have been calculated based on the slovin formula. The methods used in this research were Rose Bengal Test (RBT) for the screening test and continued with Complement Fixation Test (CFT) for the confirmation test. The results RBT of this research clearly showed that positive results from 10 samples were confirmed as a final diagnostic test of Brucellosis using CFT. CFT showed a positive result from 9 samples and negative in 1 sample. The percentage of Brucellosis occurrence in the Turen District was recorded at 11.5%. Moreover, Turen District also became an area with a high Brucellosis occurrence (>2%).